COVID-19 symptomatic community illness, hospitalization, and death burden across all ages — New South Wales, Australia, May 2021–July 2022 - Kelsey M. Sumner; Sandra Carlson; Benjamin Elton; Michelle Butler; Janaki Amin; Melissa A. Rolfes; Carrie Reed; A. Danielle Iuliano; David J. Muscatello; Craig Dalton (BMC Public Health)
Abstract Background Coronavirus disease 2019 (COVID-19) burden is difficult to quantify with cases missed by surveillance systems. During COVID-19 Delta and Omicron BA.1–5 periods, we assessed the COVID-19 burden in New South Wales (NSW), Australia, from May 2021–July 2022 using a participatory surveillance system of self-reported respiratory disease and a database of people seeking healthcare. Methods To estimate community illness burden, we adjusted the NSW age-stratified non-case population by reported severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) percent positive and acute respiratory illness (ARI) rates. Hospitalization and death burden were estimated by adjusting reported rates to the NSW population and by the proportion of COVID-19 admissions attributable to COVID-19 illness. Burden estimates were compared to reported case counts. Results From May 2021–July 2022, an estimated 3,450,516 (95%CI: 2,847,355–4,119,472) symptomatic community ARI illnesses, 24,684 (95%CI: 20,714–29,144) hospitalizations, and 4,638 (95% CI: 3,263–6,049) deaths were attributable to COVID-19 in NSW. Reported cases (3,039,239) were 14% lower than the estimated symptomatic community illness burden but within the estimate’s 95% confidence interval. Overall, 0.7% of symptomatic community illnesses resulted in hospitalization and 0.1% resulted in death. Conclusions Estimated symptomatic case hospitalization and fatality risk could be used for COVID-19 modelling and forecasting.